Oil price thresholds and stock returns. Issue 2 (3rd April 2019) - Chen, An-Sing; Yang, Che-Ming
ABSTRACT: In this article, we apply the threshold autoregressive model to examine oil price thresholds and the relationship between oil prices and the returns of 25 benchmark portfolios formed on size and book-to-market. Our results show that the relationship between the change in oil prices and portfolio returns reverses depending on whether the current oil price is above or below the estimated oil price threshold. Additional results show that this threshold effect is concentrated in the small stock portfolios. Finally, our finding that there is a threshold effect of oil price changes on stock returns is consistent with the theoretical model of investor sentiment presented by Barberis, Shleifer, and Vishny (1998) and is intuitively consistent with the economic dynamics and structure of the oil industry.